Hypomyelinating leukodystrophies — a molecular insight into the white matter pathology. Issue 4 (17th June 2016) - Charzewska, A.; Wierzba, J.; Iżycka‐Świeszewska, E.; Bekiesińska‐Figatowska, M.; Jurek, M.; Gintowt, A.; Kłosowska, A.; Bal, J.; Hoffman‐Zacharska, D.
Abstract : Hypomyelinating leukodystrophies (HLDs) are a group of neurodevelopmental disorders that affect proper formation of the myelin sheath in the central nervous system. They are characterized by developmental delay, hypotonia, spasticity, and variable intellectual disability. In the past various classification systems for HLDs have been used, based on imaging findings, clinical manifestation, and organelle‐specific disorders. Here we present a molecular insight into HLDs based on a defect in specific gene engaged in myelination. We discuss recent findings on pathogenesis, clinical presentation, and imaging related to these disorders. We focus on HLDs that are in use in differential diagnostics of Pelizaeus–Merzbacher disease (PMD), with a special emphasis on Allan–Herndon–Dudley syndrome (AHDS), an X‐linked condition with delayed myelination due to thyroid transport disturbances. On the background of previously published patients we describe a proband initially considered as presenting with a severe PMD, whose diagnosis of AHDS due to a novel nonsense SLC16A2 mutation unraveled two previously undiagnosed generations of affected males who died in infancy from unexplained reasons. Since AHDS is found to be a relatively frequent cause of X‐linked intellectual disability, we emphasize the need for determining the whole thyroid profile especially in hypotonic males with a delay of psychomotor development. Abstract :